Unmasking Organic Pathology in Pediatric Recurrent Abdominal Pain: Diagnostic Yield, Histopathological Discordance, and the Asian Enigma in a Tertiary Indonesian Setting - Doni Andika Putra; Yusri Dianne Jurnalis (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Recurrent abdominal pain (RAP) in children presents a complex diagnostic dichotomy between functional disorders and organic pathology. In Southeast Asia, this challenge is compounded by the Asian Enigma of variable Helicobacter pylori prevalence. This study evaluated the diagnostic yield of Esophagogastroduodenoscopy (EGD) and the correlation between macroscopic and histopathological findings in an Indonesian tertiary pediatric cohort. Methods: A retrospective, analytical cross-sectional study was conducted on 108 pediatric patients aged 1 to 18 years fulfilling Rome IV criteria for RAP between January 2022 and July 2025. EGD was performed, with biopsies taken based on macroscopic abnormalities or clinical suspicion (n=65). Diagnostic yield was calculated, and H. pylori prevalence was subjected to sensitivity analysis to account for non-biopsied patients. Multivariate logistic regression identified predictors of organic findings. Results: The cohort was predominantly female (65.7%) and adolescent (48.1%). The overall diagnostic yield for macroscopic abnormalities was 77.8%, dominated by macroscopic gastritis (39.8%). H. pylori infection was confirmed in 26.9% of the total cohort, rising to 44.6% (95% Confidence Interval: 32.5%–57.3%) among biopsied patients. Sensitivity analysis estimated the true prevalence range between 26.9% and 48.0%. Notably, in a subset of patients with normal macroscopic mucosa (n=10), 30% exhibited microscopic inflammation, indicating endoscopic-histologic discordance. Independent predictors of organic pathology included age over 10 years (adjusted Odds Ratio 2.41) and vomiting (adjusted Odds Ratio 3.12). Conclusion: EGD reveals a high burden of organic disease in Indonesian children with RAP, challenging the functional paradigm in this setting. The significant rate of H. pylori and potential microscopic inflammation in normal-appearing mucosa suggest that biopsy should be considered routine rather than targeted to avoid verification bias.